Qualidade de vida no/do trabalho dos profissionais da estratégia de saúde da família - Maganhoto, Aline Maria dos Santos (2021)
Introduction. The work environment found in healthcare units is constantly exposed to risk factors, biological, physical and ergometric. Given these risks and their grievances, the challenges of promotion actions are focused on reducing health inequalities. In the face of precarious working conditions, aggravated by the Covid-19 pandemic, Worker's Health must guarantee better wages and working conditions. Among this segment, there are the professionals of Primary Health Care, whose working conditions must create strategies that benefit the Quality of Life in the Work (QLW) of these professionals. Objectives. The research aimed to understand the elements that make up the Quality of Life in (d) Work from the perspectives of professionals in the Family Health Strategy in a municipality in the Triângulo Mineiro region; To present, through an Integrative Literature Review, the academic production on the quality of life of workers who work in the Family Health Strategy; Identify the socio-demographic and professional profile of workers at a Basic Family Health Unit (UBSF) in Uberlândia, MG; Diagnose which spheres of the TQWL-42 influence the QLW of APS workers; Point out the perspectives about the spheres that constitute the QLW of professionals in Primary Health Care in the city of Uberlândia. Methodology. This was research with a quantitative and qualitative approach, descriptive regarding the objectives, bibliographical and field regarding the procedures. The population consisted of 34 professionals from the participating UBSF, in the municipality of Uberlândia in the state of Minas Gerais. The research site was a Basic Health Unit in the city, defined by the Municipal Health Department. The Total Quality of Work Life questionnaire (TQWL-42) was used as a quantitative instrument, and a qualitative questionnaire prepared by the authors, containing 4 questions was used. The analysis of quantitative data took place through the SPSS software and the qualitative through thematic content analysis. Results. The integrative literature review allowed us to realize that health professionals working in the Family Health Strategy are continually exposed to stressors in their work environment. Regarding descriptive data, there was a predominance of females: 25 women (89.3%) and 3 men (10.7%). Regarding marital status, 14 participants (50%) were married, 12 (12%) were single, 1 (3.6%) widowed and 1 separated (3.6%). Related to length of experience, the group mean was 44.4 (±45.8). Regarding education, 22 (78.6%) have Complete Post-Graduation and 15 (53.6%) of the participants have Complete High School. The analysis of the Quality of Life at Work of the Family Health Strategy team showed that the professionals assessed the scores for the Spheres and the General Result as unsatisfactory with a tendency towards neutral and towards neutral/satisfactory. The narratives showed a good QLW, but with points that should be improved. Conclusion. It is concluded that the initial objective of this study was considered, as the data from this study allowed us to understand the elements that make up the Quality of Life at Work from the perspective of professionals of the Family Health Strategy in a city in the Triângulo Mineiro and it also made it possible to know the characteristics of the Quality of Life at Work of these professionals.